Digital-Based Business Licensing Reform in Indonesia: An Analysis of The Online Single Submission (Oss) Policy - Anwar Khomeni, Syamsul; Wahyudi Atmoko, Andreo (Pelopor Publikasi Akademika, 2025)
The Online Single Submission (OSS) policy is a key reform in Indonesia’s business licensing system, part of a broader digital transformation in public governance. Introduced to reduce bureaucratic complexity, accelerate service delivery, and improve transparency, OSS aims to enhance legal certainty for businesses. This study examines the OSS policy through public administration reform by analyzing its regulatory design, implementation mechanisms, outcomes, and challenges. A narrative policy review approach was used, including literature analysis of regulations, scholarly articles, policy reports, and government documents, with a descriptive-qualitative analysis. Findings show that OSS aligns with e-government and good governance principles, contributing to faster licensing, integration of business data via the Business Identification Number (NIB), and improved service transparency. The risk-based licensing approach marks a shift from administrative control to a more adaptive and proportional regulatory model. However, challenges remain, including regulatory disharmony between central and local governments, limited bureaucratic capacity, unequal digital infrastructure, and low digital literacy among MSMEs. Data governance and cybersecurity issues also remain significant concerns. In conclusion, while OSS is a strategic policy tool for reforming business licensing, its full potential is not yet realized. Strengthening institutional capacity, improving regulatory coherence, enhancing digital literacy, and expanding technological infrastructure are vital for the sustainability and effectiveness of Indonesia's digital governance reform.